Circulating microRNAs as potential cancer biomarkers: the advantage and disadvantage - Hao Wang; Ran Peng; Junjie Wang; Zelian Qin; Lixiang Xue (Clinical Epigenetics, 2018)
Abstract MicroRNAs are endogenous single-stranded non-coding small RNA molecules that can be secreted into the circulation and exist stably. They usually exhibit aberrant expression under different physiological and pathological conditions. Recently, differentially expressed circulating microRNAs were focused on as potential biomarkers for cancer screening. We herein review the role of circulating microRNAs for cancer diagnosis, tumor subtype classification, chemo- or radio-resistance monitoring, and outcome prognosis. Moreover, circulating microRNAs still have several issues hindering their reliability for the practical clinical application. Future studies need to elucidate further potential application of circulating microRNAs as specific and sensitive markers for clinical diagnosis or prognosis in cancers.